IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KABUPATEN CIREBON - Hardiyansyah, Rakhmat; Amin, Muhammad (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Efforts to implement poverty reduction policies in Cirebon Regency require the active role of various stakeholders to reduce poverty, the purpose of this study is to analyse the process and outcomes of poverty reduction policy implementation in Cirebon regency in order to formulate appropriate poverty reduction policies. Qualitative methods were used to identify the drivers of poverty reduction policy implementation from the perspective of policy makers and the poor in Cirebon regency. Data analysis was carried out using triangulation techniques, namely data reduction, data presentation and inference. The results of the study showed that the process of poverty reduction policy implementation was carried out by the Cirebon District Poverty Reduction Coordination Team. The poor in Cirebon County receive various types of assistance, but the implementation of poverty reduction policies often fails due to insufficient funding, weak supervision and invalid data. They want transparency about aid recipients, as well as training and business capital. This study highlights the importance of communication and the role of bureaucratic structures in achieving transparency in poverty reduction policies.